Critically ill children with SARS-COV-2 Omicron infection at a national children medical center, Guangdong, China - Fen Lin; Dao-Ju Jiang; Song Zhang; Zhe Yang; Hua-Song Zeng; Zhi-Ping Liu; Li-Ye Yang (BMC, 2024)
Abstract Background SARS-CoV-2 infection is described as asymptomatic, mild, or moderate disease in most children. SARS-CoV-2 infection related death in children and adolescents is rare according to the current reports. COVID-19 cases increased significantly in China during the omicron surge, clinical data regarding pediatric critical patients infected with the omicron variant is limited. In this study, we aim to provide an overview of the clinical characteristics and outcomes of critically ill children admitted to a national children's medical center in Guangdong Province, China, during the outbreak of the omicron variant infection. Methods We conducted a retrospective study from November 25, 2022, to February 8, 2023, which included 63 critically ill children, under the age of 18, diagnosed with SARS-CoV-2 infection. The patients were referred from medical institutions of Guangdong province. The medical records of these patients were analyzed and summarized. Results The median age of patients was 2 years (Interquartile Range, IQR: 1.0-8.0), sex-ratio (male/female) was 1.52. 12 (19%) patients (age ≥ 3 years) were vaccinated. The median length of hospital stay was 14 days (IQR: 6.5-23) in 63 cases, and duration of fever was 5 days (IQR: 3-8.5), pediatric intensive care unit (PICU) stay was 8 days (IQR 4.0-14.0) in 57 cases. 30 (48%) cases had clear contact history with family members who were infected with SARS-CoV-2. Three children who tested positive for SARS-CoV-2 infection did not show any abnormalities on chest imaging examination. Out of the total patients, 33 (52%) had a bacterial co-infection, with Staphylococcus aureus being the most commonly detected bacterial pathogen. Our cohort exhibited respiratory and nervous system involvement as the primary features. Furthermore, fifty (79%) patients required mechanical ventilation, with a median duration of 7 days (IQR 3.75-13.0). Among these patients, 35 (56%) developed respiratory failure, 16 (25%) patients experienced a deteriorating progression of symptoms and ultimately succumbed to the illness, septic shock was the most common condition among these patients (15 cases), followed by multiple organ failure in 12 cases, and encephalopathy identified in 7 cases. Conclusion We present a case series of critically ill children infected with the SARS-CoV-2 omicron variant. While there is evidence suggesting that Omicron may cause less severe symptoms, it is important to continue striving for measures that can minimize the pathogenic impact of SARS-CoV-2 infection in children.